The truth about creating brands people love - Till, Brian 1960- (Truth about, 2009)
The quick, complete, easy-to-use guide to brand management!- 51 bite-size, fast-paced insights and realistic solutions for building any brand in any marketplace.- Coverage of everything that matters, from positioning through packaging, marketing through metrics.